2006
DOI: 10.1359/jbmr.060704
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Paget's Disease in Europe: The Prevalence Is Decreasing

Abstract: This study estimated changes in the age-and sex-specific prevalence of Paget's disease of bone in six European towns over a 20-year period. Declines in prevalence were observed in this disorder, occurring among both men and women.Introduction: To estimate secular changes in the age-and sex-specific prevalence of Paget's disease of bone in Europe, we conducted a second radiographic survey using identical sampling and methods in six European towns where a baseline study was performed in [1978][1979]. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 32 publications
5
81
0
5
Order By: Relevance
“…According to several studies [1,2], the described time trends of PDB have revealed: (i) a decline of the frequency of PDB in recent years; however, it should also be stressed that there have been major changes in the ethnic make-up of the population in UK over the past 25 years with an influx of people from the Indian subcontinent and Asia, more in general, which could account at least in part for the described reduced prevalence. Moreover, as PDB diagnosis in the past was accidentally performed, in particular in asymptomatic or slightly symptomatic forms, when classical radiology was intended to evaluate abdominal symptoms, back pain, pelvic pain or hip pain, the advent of ultrasonography in evaluating abdominal disorders, such as gallstones and kidney stones, has supplanted the traditional radiology in the diagnosis of these diseases and consequently reduced the possibility of accidentally identifying a bone disease such as PDB.…”
Section: Secular Trends Of Paget's Disease Of Bone: Conflicting Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to several studies [1,2], the described time trends of PDB have revealed: (i) a decline of the frequency of PDB in recent years; however, it should also be stressed that there have been major changes in the ethnic make-up of the population in UK over the past 25 years with an influx of people from the Indian subcontinent and Asia, more in general, which could account at least in part for the described reduced prevalence. Moreover, as PDB diagnosis in the past was accidentally performed, in particular in asymptomatic or slightly symptomatic forms, when classical radiology was intended to evaluate abdominal symptoms, back pain, pelvic pain or hip pain, the advent of ultrasonography in evaluating abdominal disorders, such as gallstones and kidney stones, has supplanted the traditional radiology in the diagnosis of these diseases and consequently reduced the possibility of accidentally identifying a bone disease such as PDB.…”
Section: Secular Trends Of Paget's Disease Of Bone: Conflicting Resultsmentioning
confidence: 99%
“…It has been suggested that patients with SQSTM1 ⁄ p62 mutations may exhibit a more severe phenotype (earlier onset and greater skeletal extent) than patients without mutations, and truncating mutations tend to cause a more severe phenotype than missense mutations [2,8,45,55].…”
Section: Sqstm1 ⁄ P62 Mutations: Genotype ⁄ Phenotype Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha descrito una agregación familiar entre un 15% y un 40% de los pacientes (8) y en estos casos la enfermedad se transmite de forma autosómica dominante con una penetrancia variable. En los últimos 15 años, varios estudios en diferentes poblaciones han observado un descenso tanto en la prevalencia como en la gravedad de la enfermedad (9,10). Se desconocen las razones de este descenso, pero podría estar en relación con los movimientos migratorios, la disminución de la consanguinidad y carga genética y con cambios en los factores ambientales.…”
Section: La Enfermedad De Pagetunclassified
“…It is still debatable in the literature if paramyxoviruses (particularly measles and canine distemper) infection in childhood is the cause of PDB and, thus, the extensive vaccination against measles led to the decline of the disease's prevalence over the last decades 2 . Furthermore, several studies indicate mutations in the SQSTM1 gene as a predisposing genetic factor in some patients 3 .…”
Section: Introductionmentioning
confidence: 99%